Spectrum analysis of OFDM versus FBMC in 5G mobile communications - Aarab Mohamed Nassim; Chakkor Otman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
With the demand for mobile data traffic, multi-carrier transmission techniques are highly attractive for all-new wireless communication systems, which divides data into many components and sends each of these components via a different carrier signal. So far, orthogonal frequency division multiplexing (OFDM) and filter bank multi-carrier (FBMC) techniques are the dominant waveform contenders. A number of studies have been made and failed to give a complete comparison where they did not consider various conditions altogether. Therefore, this paper addresses a complete comparative analysis of OFDM and FBMC, performed based on spectral efficiency, modulation, demodulation, power spectral densities, and peak to average power ratio comparison, all simulated using Matlab and GNU’s not unix radio (GNU-radio) software.